Precarização das relações de trabalho na era digital : uma reflexão à luz da teoria do reconhecimento de Axel Honneth - Barth, Fernanda Daniela (2023)
The dissertation aims to develop a reflection on the precariousness of labor relations in the digital era based on the Theory of Recognition from Axel Honneth. The intention is to inquire about the relevance of this theory in this era, to then support emancipatory movements that lead to the rescue of the worker’s dignity. For that, the world of work in post-modernity; the devastation of the world of work; Hartmut Rosa's theory of social acceleration; Byung-Chul Han's performance society, the advent of Industry 4.0, and the corrosion of the dignity of work, resorting, in particular, to the works of sociologist Ricardo Antunes, are analyzed. From this study, in which certain aspects of the post-modernity were established, it is off to the analysis of the theory of recognition from Axel Honneth, using as a theoretical reference his book "Struggle for Recognition," which analyzes the relations of recognition, as well as its forms of disrespect that may or may not motivate the struggle of recognition. Next, the hypotheses in which experiences of disrespect will be enough to trigger the motivation to fight for recognition in the labor field are analyzed. In conclusion, it is pointed out that the Honnethian theory is still relevant to support social movements that allow workers to find their moral and political space in the current world of work and create possibilities for action and resistance, nevertheless, it can be understood as a social theory in constant elaboration